Determinants of Green Purchase Intention and Willingness to Pay a Premium: An Extension of the Theory of Planned Behavior - Purwianti, Lily; Indah, I.; Lady, L. (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
Drawing on an extension of the Theory of Planned Behavior (TPB), this research investigates the factors influencing green purchasing intention (GPI) and willingness to pay a premium (WPP) for eco-friendly items. Two explanatory variables in the suggested framework are ethical obligation (EO) and environmental concern (EC). Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze data from 395 respondents, collected via a five-point Likert scale. According to the findings, EO and SN significantly boost GPI and WPP, whereas EC has a direct effect on GPI but none on WPP. Also, there seems to be an attitude-behavior gap between how environmentally concerned customers are and how much they are ready to pay for products, as the correlation between GPI and WPP is not very strong. These results emphasize the significance of ethical and societal considerations in shaping environmentally conscious purchasing decisions. This research has practical applications for marketers, enabling them to highlight ethical principles and social impact while marketing environmentally friendly goods, and it contributes to TPB's expansion by incorporating ethical issues.